KUR'AN'DA TUHR KAVRAMI - BULUT, AHMET (Fırat Üniveristesi, 2011)
Her şeyin özü olan temizliği ifade eden ?tuhr? kavramı, sözlükte; temiz ve arı olmak, kadının adeti kesilmek, bir şeyi arıtmak, temizlemek, dezenfekte etmek, temizlenmek, yıkanmak, günahlardan, çirkinliklerden ve yerilen tüm hal ve hareketlerden sakınmak, tövbe vs. malî ve bedenî ibadetlerle nefsi günahlardan temizlemektir.Fıkıhta temizlik, ibadet etmeye engel durumların kalkması veya giderilmesi diye tanımlanırken; itikatta temizlik, kişinin inancını her türlü şirk, küfür, riya gibi imana munakız durumlardan arındırmasıdır. Ahlakta temizlik ise, kişinin kalbini ve niyetini masivadan temizleyip, ihlasa bürünüp ahlakını güzelleştirmesidir.?Tuhr? kavramının Kur'an'daki kullanımları, maddî, manevî ve hükmî temizlik türlerinin hepsini kapsamaktadır. Maddî temizlik, beden ve elbisenin, mekânın, havanın ve suyun her türlü maddî kirlilikten temizlenmesidir. Manevî temizlik, itikadın, kalbin, niyetin ve ahlakın her türlü şirk ve günah kirlerinden arındırılmasıdır. Hükmî temizlik ise, namaz ve tavaf gibi ibadetlerde istenen abdest ve gusül temizliğidir.Kur'an'ın bizden istediği, her yönüyle temizliği kuşanıp temiz birey, temiz toplum, temiz çevre olgusunu hayata geçirmek ve selim fıtratı muhafaza etmektir.Anahtar Kelimeler: Tuhr, temizlik, maddî, manevî, hükmî, psikolojik.

The concept of tuhr, which denotes cleanliness, the essence of everything, literally means: to be clean and pure; to recover from menstruation; to purify, clean, and disinfect something; to get cleaned, washed; to avoid all sins and bad things, and all the situations and behaviors, to repent, to get cleansed by performing financial and bodily services.While in Islamic jurisprudence cleanliness is defined as removing the situations that legally prevent the performance of religious services, in Islamic creed it is defined as purging one?s belief from qualities that contradict belief, such as şirk (associating other deities with God), kufr (blasphemy), and riya (pharisaism). In ethics, it denotes one?s cleaning one?s heart and intention from all things other than God, practicing sincerity and mbellishing one?s morality.The uses of the concept of ?tuhr? in Koran comprise all theree kinds of physical, spiritual and legal/nominal cleanliness. Physical cleanliness is purification of the body, the attire, the space, the weather, and water from all kinds of physical dirt and filth. Spiritual cleanliness is the purification of the creed, the heart, the intention and the morality from the dirt of all kinds of şirk and sin. Legal/nominal cleanliness, on the other hand, refers to the ritual purity ?such as ablution and bodily ablution- required for performance of such services as prayer and tavaf.What Koran demands from us is to be equipped with cleanliness in all its senses and to realize the ideal of clean individual, clean society, and clean environment, and thus to preserve the uncorrupted human nature.Key Words: Tuhr, Cleanliness, physical, spiritual, legal/nominal.
The concept of tuhr [cleanliness] in the Koran
Keywords: Din